Triggering mechanism of an eruptive filament located in a weak active region - Zou, Peng; Jiang, Chaowei; Bian, Xinkai; Wang, Juntao (Frontiers in Astronomy and Space Sciences, 2024)
IntroductionThe triggering mechanism for filaments located in a weak magnetic field typically leans toward magnetohydrodynamic instabilities due to the weak magnetic strength inherent in filament structures. However, a subset of eruption events associated with significant flares remains. Therefore, we seek to understand the role that reconnection plays in the eruption of filaments with weak magnetic fields.MethodsWe reconstruct the coronal magnetic field of an eruptive filament located in a relatively weaker magnetic environment, and analyze the magnetic field properties such as twist number and squashing factor.ResultsThis filament remains stable until the expansion of the heated bright arcades underneath. This expansion initially activates the filament, prompting its upward movement, leading to a gentle reconnection slightly to its south. The ensuing reconnection continues to propel the filament upward with uniform acceleration. These upward motions cause the drainage of filament mass, likely activating the torus instability of the filament. This torus instability then triggers the final eruption of the filament, successfully generating a coronal mass ejection (CME) and leaving behind a double-ribbon flare.DiscussionWe conclude that the torus instability serves as the primary triggering mechanism of this eruption, while pre-eruption reconnection plays a role in pushing the filament upward to meet the instability condition.